NIMG-54. DIFFUSION MRI PHENOTYPES PREDICT OVERALL SURVIVAL BENEFIT FROM BEVACIZUMAB IN RECURRENT GLIOBLASTOMA WITH A LARGE TUMOR BURDEN: EVIDENCE FROM CLINICAL PRACTICE AND A MULTICENTER PHASE 3 TRIAL. (11th November 2019) - Patel, Kunal; Raymond, Catalina; Yao, Jingwen; Tsung, Joseph; Goldman, Jodi; Schlossman, Jacob; Tran, Caleb; Brenner, Andrew; Butowski, Nicholas; Wen, Patrick; Pope, Whitney; Ji, Matthew; et al.
Abstract: We have previously shown that diffusion MR characteristics are a predictive imaging biomarker for survival benefit in recurrent glioblastoma treated with anti-VEGF therapy; however, contemporary clinical use of bevacizumab is often limited to patients with very large tumors and/or after multiple recurrences. We hypothesize that diffusion MR characteristics can be used to predict long-term survival benefit in these patients, which may be beneficial for clinical decision-making. The current study identified 83 recurrent glioblastoma patients from our institution who were treated with bevacizumab over the past 5 years with high quality anatomic and diffusion MRI data. Of these 83 patients, 35 had large contrast enhancing tumors (>20cc or >3.4cm diameter, group average). Additionally, we identified 37 recurrent glioblastoma patients from the bevacizumab treated control arm of a recent multicenter phase III trial (NCT02511405) with high quality data and large enhancing tumors for validation. Pre-treatment tumor volume was quantified using T1 subtraction maps and apparent diffusion coefficient (ADC) histogram analysis was used to phenotype patients as having high (> 1.24 um2/ms) or low (< 1.24 um2/ms) ADCL, the mean value of the lower peak using a double Gaussian mixed model. Median overall survival in patients with large volume recurrent glioblastoma was 5.7 months. High ADCL was associated with significantly longer overall survival (OS) compared with low ADCL in both single center (P=0.0271, HR=0.486, mOS=5.5 vs. 2.8mo) and multicenter phase III data (P=0.0457, HR=0.507, mOS=7.9 vs. 5.7mo). Accounting for absolute tumor volume and age, both cohorts showed that ADCL was an independent prognostic factor for OS (Cox, P< 0.01). In summary, pre-treatment diffusion MR imaging is an independent predictive biomarker for OS in recurrent glioblastoma with a large tumor burden.